Torta de filtro e lodo de esgoto na composição de fertilizantes organominerais para a cultura da soja - Silva, Leidyanne Godinho (2017)
Soybean cultivation is significantly affected by environmental and nutritional changes during its growing cycle. The use of organic mineral fertilizers is a viable alternative to achieve high yields in different regions of the country. The aim of this study was to assess the efficiency of organic mineral fertilizers formulated from sanitized sewage sludge and filter cake in soybean cultivation, using phenometric and biochemical assessments. The experiment was conducted in 10L plastic pots, in a greenhouse located at the Patos de Minas University Center, in the municipality of Patos de Minas, Minas Gerais state, Brazil. A randomized block design was used with a 2 x 4 factorial scheme, represented by two sources of organic matter to form the organic mineral fertilizer (sewage sludge and filter cake), for doses of 50, 75, 100 and 125% in relation to the 120 kg ha-1 dose of P2O5 recommended for the field. The NA 5909 RG cultivar (Nidera®) was used and inoculated with CoMo Platinum® (1.5 mL kg-1) + Standak Top® (2 mL kg-1) before planting. Accumulated root, stem, leaf and pod dry mass were measured at 30, 60 and 80 days after planting. Analyses of the antioxidant metabolism of catalase enzymes, superoxide and peroxidase dismutase, hydrogen peroxide content, proline, and lipid peroxidation were conducted at 45 days after planting, in addition to production at the end of the cycle. The results obtained were submitted to the test of normality and homogeneity of variances. Tukey’s test, at 5% significance, was used to compare doses and the Dunnett test to compare all treatments with the treatment without fertilizer and mineral fertilizer. Applying 75% sewage sludge organic mineral fertilizer caused an increase in stem dry matter compared to mineral fertilizer, on all the dates analyzed. For leaf dry mass at 80 days after planting, all the treatments with organic mineral fertilizer were superior to those without fertilizer and with mineral fertilizer. With respect to pod dry mass, only 75% filter cake organic mineral fertilizer was superior to mineral fertilizer. The use of organomineral fertilizers promoted increased activity of the enzyme catalase. The fertilization with organomineral fertilizer in the formulation of 125% of filter cake provided an increase in the content of lipid peroxidation in soybean plants. Based on the data obtained in the present study, it was possible to verify that the use of filter cake and sanitary sewage sludge in the 12 formulation of organomineral fertilizers satisfactorily replaces the use of mineral fertilizers for the soybean crop.